Profil Industri Rumah Tangga Spesifik Lokal Di Kecamatan Abang Kabupaten Karangasem, Provinsi Bali - Astiti, Ni Wayan Sri; Darmawan, Dwi Putra; Sarjana, Dewa Raka (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2016)
Policy of empowerment of the rural poor by involving the activ participation of all stakeholders, including women, is a comprehensive approach to the development of the creative economy in Bali. Karangasem regency is one of the districts with the largest number of poor people in the province of Bali. The purpose of this research is:  Identify the typologi of domestic industry (IRT). The research methodology using descriptive analysis method.The analysis showed the following matters: Propyl IRT is characterized by several components, namely; (A) the characteristics of businesses IRT dominated by women with an average age of 38.6 years, mostly housewives. (B) Based on IRT propyl clusters are grouped into: (1) Handicraft (woven palm, bamboo and coconut shells) some 70%; (2) Food and beverage industry (10%), (3) Industrial equipment ceremony (cymbals cider and offerings) by 7%; (4) Other industries (13%). (C) Based on the stage of development. The typologi business, namely (1) Industrial Business beginners (90%); (2) The business industry is growing (10%), and (3) advanced industrial enterprises (0%).
Keywords: Household Industry (IRT), profiles, typology, women